2019
DOI: 10.1042/bsr20190625
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel genes associated with a poor prognosis in pancreatic ductal adenocarcinoma via a bioinformatics analysis

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a class of the commonest malignant carcinomas. The present study aimed to elucidate the potential biomarker and prognostic targets in PDAC. The array data of GSE41368, GSE43795, GSE55643, and GSE41369 were downloaded from Gene Expression Omnibus (GEO) database. The differentially expressed genes (DEGs) and differentially expressed microRNAs (DEmiRNAs) in PDAC were obtained by using GEO2R, and overlapped DEGs were acquired with Venn Diagrams. Functional enrichment anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 62 publications
6
45
0
Order By: Relevance
“…It was con rmed that the high expression of miR-744 was signi cantly related to lymph node metastasis and poor prognosis of NSCLC, and was an independent prognostic molecular marker of NSCLC. This is comparable to ndings in the studies on pancreatic cancer [19][20][21], prostate cancer [23,24] and nasopharyngeal carcinoma [4,36]. All of these suggested that miR-744 might play an important role in the process of NSCLC progression and metastasis, and need to be further studied.…”
Section: Discussionsupporting
confidence: 85%
“…It was con rmed that the high expression of miR-744 was signi cantly related to lymph node metastasis and poor prognosis of NSCLC, and was an independent prognostic molecular marker of NSCLC. This is comparable to ndings in the studies on pancreatic cancer [19][20][21], prostate cancer [23,24] and nasopharyngeal carcinoma [4,36]. All of these suggested that miR-744 might play an important role in the process of NSCLC progression and metastasis, and need to be further studied.…”
Section: Discussionsupporting
confidence: 85%
“…[14][15][16] High expression of miR-196a, miR-27a, miR-221, miR-143, miR-135b, miR-199b-5p and miR-21, but low expression of miR-744, miR-455-3p and miR-655, in pancreatic cancer samples were found compared with normal samples and associated with poor prognosis. 17 In addition, the expression profile of miRNAs varies even in the different locations, 18 which further confirms that miRNAs have high application value in the diagnosis, prognosis evaluation and treatment of pancreatic cancer. Recently, a widely reported miRNA, miR-939, has been pointed out to be pivotal in the development and procession of cancers, such as hepatocellular carcinoma, 19 tongue squamous cell carcinoma, 20 gastric, 21 lung, 22 colorectal, 23 and ovarian cancer.…”
Section: Introductionmentioning
confidence: 75%
“…Meanwhile, a large number of cancer-related data are stored in publicly available databases, such as The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO). A reanalysis of these data could facilitate the discovery of a vast range of valuable biological information (Gao et al, 2018(Gao et al, , 2019Liu et al, 2019;Zhou et al, 2019). For instance, several novel genes associated with poor prognosis of patients with pancreatic ductal adenocarcinoma (PDAC) were identified by analyzing the array data from GEO.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, several novel genes associated with poor prognosis of patients with pancreatic ductal adenocarcinoma (PDAC) were identified by analyzing the array data from GEO. These genes might serve as potential diagnostic and prognostic biomarkers for PDAC (Zhou et al, 2019). Liu et al (2019) revealed a novel robust four-gene metabolic signature predicting overall survival for hepatocellular carcinoma (HCC) by mining mRNA expression profiles and clinicopathological data from TCGA and GSE14520 data sets.…”
Section: Introductionmentioning
confidence: 99%